Ekspektansi Performa dan Ekspektansi Usaha sebagai Prediktor terhadap Niat Perilaku Konsumen Blibli di Jakarta - Bryan Nathanael; Richard Andrew (PT. Hasba Edukasi Mandiri, 2026)
This study aims to analyze performance expectancy and effort expectancy as predictors of behavioral intention among Blibli consumers in Jakarta amid increasing competition in the e-commerce industry. This study employs a quantitative approach with a descriptive design and collects data through questionnaires administered to 100 respondents who meet the specified criteria. The relationships among variables are examined using the Structural Equation Modeling (SEM) method through SmartPLS 4. The results show that performance expectancy is a positive and significant predictor of behavioral intention, indicating that perceived benefits and performance improvements from using the Blibli application increase consumers’ intention to continue using it. In addition, effort expectancy is also proven to be a positive and significant predictor of behavioral intention, suggesting that the ease of use of the application influences consumers’ decisions to continue using the platform. These findings emphasize the importance of application ease of use and perceived benefits in driving consumers’ behavioral intention, while also providing practical implications for Blibli to enhance user experience and maintain competitiveness in the e-commerce market.